Words, Music, and Propaganda: Book of Abstracts (University of Maribor Press, 2022)
The fifth Words and Music conference, organized by the English Department of the Faculty of Arts and the Music Department of the Faculty of Education at the University of Maribor, explores the relation between words, music and propaganda, and the place of that relation in history and in modern contemporary culture. The conference includes presentations from the fields of musicology, history, anthropology, sociology, psychoanalytic theory, Marxism, feminist theory, and translation studies, and from different critical perspectives, such as literary and linguistic analysis, Gender Studies, ethnomusicology, critical musicology, stylistics, and popular music studies, applied to genres including folk and protest music, American and European jazz, popular and classical music, rock, and rap.